Late Victorian Crime Fiction in the Shadows of Sherlock - Clarke, C. author. aut Link
VIII, 221 p.
Keywords: This book investigates the development of crime fiction in the 1880s and 1890s, challenging studies of late-Victorian crime fiction which have given undue prominence to a handful of key figures and have offered an over-simplified analytical framework, thereby overlooking the generic, moral, and formal complexities of the nascent genre.